THE IMPACT OF PINEAPPLE (ANANAS COMOSUS (L.) MERR.) JUICE ON FUNDAL HEIGHT IN PRIMIGRAVIDA MOTHERS DURING POSTPARTUM PERIOD - Winda Yunyaty Harianja; Onny Setiani; Umaroh Umaroh; Melyana Nurul Widyawati; Imam Djamaludin Mashoedi; Sri Endang Pujiastuti (Belitung Nursing Journal, 2017)
Background: Failure in the process of uterine involution can result in bleeding if not treated immediately. Provision of pineapple (Ananas Commosus (L). Merr) juice can be administered as a medicinal plant therapy to prevent sub involution of the uterus and is considered to speed up the recovery process of the uterine involution. Objective: This study aims to examine the effect of pineapple (Ananas Commosus (L). Merr) juice to decrease fundal height in primigravida mothers during postpartum period. Design: This was a quasi-experimental study with non-equivalent control group, conducted in the working area of the Health Center (Puskesmas) of Jekulo Kudus Indonesia on 1-30 December 2016. There were 28 respondents selected using consecutive sampling technique, consisted of 14 respondents in the intervention group and 14 respondents in the control group. Data were analyzed using independent t-test and paired t-test. Results: Findings showed that there was a mean difference of the height of the uterine fundus after given pineapple juice in the intervention group with mean score 13.80 in pretest and 5.80 in posttest, while there was also a decrease in fundal height in the control group with mean score 13.35 in pretest and 7.01 in posttest. The mean of fundal height in the intervention group was 8.15 cm and in the control group was 6.09 cm in 7 days. There was significant difference of the average of the decrease of fundal height between both groups with p-value (0.000). Conclusions: Pineapple (Ananas comosus (L.) Merr) juice had a significant effect in the decrease of fundal height. It is suggested that pineapple juice can be used as herbal or medicinal plants, which can be used during postpartum period that is processed naturally without involving the use of chemical and incorporated into the procedure standard of midwives in postnatal care.